2018
DOI: 10.3171/2016.12.jns161039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment modality on in-hospital outcome in patients with subarachnoid hemorrhage: a nationwide study in Japan (J-ASPECT Study)

Abstract: ABBREVIATIONS BRAT = Barrow Ruptured Aneurysm Trial; CCI = Charlson Comorbidity Index; CSC = comprehensive stroke center; DPC = Diagnosis Procedure Combination; HAC = hospital-acquired condition; ISAT = International Subarachnoid Aneurysm Trial; JCS = Japan Coma Scale; mRS = modified Rankin Scale; PPV = positive predictive value; PSI = patient safety indicator; RCT = randomized controlled trial; SAH = subarachnoid hemorrhage. OBJECTIVE Although heterogeneity in patient outcomes following subarachnoid hemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 35 publications
2
40
1
Order By: Relevance
“…In contrast, better Abbreviations: OR, Odds ratio; CI, confidence interval; EPA, eicosapentaenoic acid functional outcomes after coiling were noted in the non-elderly when compared with the elderly group. Previously, we have shown that in-hospital mortality rates in clipping patients after aSAH in Japan are significantly lower than those in the other countries, while in-hospital mortality rates after coiling are comparable [22]. The present study showed that the relative Although coiling was used more frequently in the elderly when compared with the nonelderly, the proportion of patients who underwent coiling in both groups were similar to that of two previous studies [23,24] that were conducted relatively soon after the publication of the International Subarachnoid Aneurysm Trial (ISAT) [25]; however, our rates were lower than a recent US report [26].…”
Section: Effects Of Treatment Modality On Clinical Outcome After Asahmentioning
confidence: 78%
“…In contrast, better Abbreviations: OR, Odds ratio; CI, confidence interval; EPA, eicosapentaenoic acid functional outcomes after coiling were noted in the non-elderly when compared with the elderly group. Previously, we have shown that in-hospital mortality rates in clipping patients after aSAH in Japan are significantly lower than those in the other countries, while in-hospital mortality rates after coiling are comparable [22]. The present study showed that the relative Although coiling was used more frequently in the elderly when compared with the nonelderly, the proportion of patients who underwent coiling in both groups were similar to that of two previous studies [23,24] that were conducted relatively soon after the publication of the International Subarachnoid Aneurysm Trial (ISAT) [25]; however, our rates were lower than a recent US report [26].…”
Section: Effects Of Treatment Modality On Clinical Outcome After Asahmentioning
confidence: 78%
“…Briefly, the JCS score consists of four main categories: alert (0) and one-, two-, or three-digit codes based on degree of arousal, each of which has three subcategories. Although previous studies have indicated that JCS score correlates with outcomes in stroke patients [10, 15], the JCS has not been examined among trauma patients.…”
Section: Introductionmentioning
confidence: 99%
“…In our cohort, seven patients (5.9%) died due to withdrawal of life support per patient wishes or family decision to prevent futile care and prolonged suffering. Case fatality was 11.8% (3.8–19.9%) lower in Japan than it was in Europe, the USA, Australia, and New Zealand ( 1 , 28 ). However, the hospital LOS in Japan was more than 10 days longer, suggestive of prolonged life support for poor grade patients with terminal illness ( 28 ).…”
Section: Discussionmentioning
confidence: 86%